2010
DOI: 10.15517/rbt.v59i1.3189
|View full text |Cite
|
Sign up to set email alerts
|

On Mellitella stokesii and Amphipholis geminata (Echinodermata), from an intertidal flat in the upper Gulf of Nicoya estuary, Pacific, Costa Rica

Abstract: Information on changes over time in the biodiversity and ecology of tropical systems is of increasing importance against the background of local, regional, and global dynamics. This study aimed to contribute with long-term data on the abundance fluctuations of two species of echinoderms from a tropical tidal flat. From February 1984 to December 1986, March 1985 to April 1987, and July 1994 to September 1996, core samples (17.7cm 2 , 15cm deep) were collected at low tide at a mud-sand flat in the mid upper Gul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
0
6
0
6
Order By: Relevance
“…More recent studies have also shown high densities in species belonging to other genera, such as Scaphechinus mirabilis from Japan (30 inds./m 2 , Matsuda et al. 2008; 160–320 inds./m 2 , Takeda 2008), or Mellitella stokesii from the Pacific coast of Costa Rica (35 inds./m 2 , Vargas & Solano 2011). Dense clypeasteroid beds may persist in the same place on the seafloor for several years, even decades (Chia 1969; Merrill & Hobson 1970; Birkeland & Chia 1971; Takeda 2008), exceeding the life expectancy of the individual sand dollars, which has been estimated in 5–9 years depending on species (Birkeland & Chia 1971; Smith 1984; Steimle 1989).…”
Section: Discussion and Taphonomic Implicationsmentioning
confidence: 93%
“…More recent studies have also shown high densities in species belonging to other genera, such as Scaphechinus mirabilis from Japan (30 inds./m 2 , Matsuda et al. 2008; 160–320 inds./m 2 , Takeda 2008), or Mellitella stokesii from the Pacific coast of Costa Rica (35 inds./m 2 , Vargas & Solano 2011). Dense clypeasteroid beds may persist in the same place on the seafloor for several years, even decades (Chia 1969; Merrill & Hobson 1970; Birkeland & Chia 1971; Takeda 2008), exceeding the life expectancy of the individual sand dollars, which has been estimated in 5–9 years depending on species (Birkeland & Chia 1971; Smith 1984; Steimle 1989).…”
Section: Discussion and Taphonomic Implicationsmentioning
confidence: 93%
“…On average, the sediments at the flat were 65% sand and about 35% mud. Other information on environmental data is included in Vargas (1987Vargas ( ,1988Vargas ( ,1989 and Vargas & Solano (2011).…”
Section: Resultsmentioning
confidence: 99%
“…From 1980 to 1983, an ecological survey was conducted in the Gulf of Nicoya estuary to provide baseline information on the Gulf in support of management policies. Many papers covering the fields of physical, chemical and biological oceanography were published (see references in Vargas & Mata 2004) making this embayment one of the better known tropical estuaries worldwide (Vargas & Solano 2011). These studies were followed by a three year survey of an intertidal 400m 2 plot in the mid upper estuary (Vargas 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Information on environmental data is included in Vargas (1987Vargas ( , 1988Vargas ( , 1989a, Vargas & Solano (2011), and Vargas-Zamora & SibajaCordero (2011). In summary: sediment composition was on the average 65% sand and 32% silt+clay.…”
Section: Uncaged Sedimentsmentioning
confidence: 99%